Securing a fair trial through exclusionary rules: do theory and practice form a well-balanced whole? - Knickmeier, Susanne (Do exclusionary rules ensure a fair trial?, 2019)
This chapter describes practitioners’ understanding of excluding illegally obtained evidence. To gain deeper insight into the applicability of the exclusion of evidence obtained through illegal means and to evaluate regulations that have been implemented, fourteen experts from different legal professions (lawyers, judges, prosecutors) and countries (Germany, Singapore, Switzerland and Taiwan (ROC)) were interviewed about their experiences. All legal systems are faced with the use of illegally obtained evidence. Based on qualitatively analyzed data the frequency of the applicability of exclusionary rules, the types of cases in which they are seen, and experts’ attitudes towards the function of exclusionary rules are described. Violations of rules around the gathering of evidence is a highly sensitive topic, particularly as the state (represented by police officers and prosecutors) plays a central and powerful role. To find out if exclusionary rules do indeed result in a more impartial trial or if further protective measures are required, factors influencing the procurement of evidence and the decision-making process around the legality of such procurement were evaluated. Subsequently, difficulties that law enforcement agencies and criminal courts are faced with were outlined, with an emphasis on the application of the law and the limitations in safeguarding criminal investigations and proceedings. Concluding remarks highlight best practices in securing a fair trial as well as ancillary measures (including unwritten techniques) that may be utilized to optimize the utility of exclusionary rules.